(untitled) (Research, Society and Development, 2022)
The research focuses on investigating education of deaf students as an essential service, capable of making them citizens with an identity, knowledge of their places and being part of a space, thus eliminating barriers that prevent them from being builders of their personal and social development in society, specifically in the educational field. Making this education accessible to all, with methodologies, instruments, professionals and the Brazilian Sign Language - Libras, in promoting inclusion, equity and quality of education for deaf students in the basic education of schools in the municipality of Tutóia – MA. The article proposes to show the reality or utopia of the LIBRAS interpreter in the education of the deaf students. The work was developed with a descriptive exploratory investigation based on reports of experiences in three schools in the municipality in the year 2021, with a qualitative approach. To certify the study, Google Scholar and Scielo platform and literary review in general were used. As a result, the literary review and observations in schools, found the non-presence of the Libras interpreter. The active teachers know about the existence of the signed language, but they do not have practical knowledge that favors the teaching process in the two languages guaranteed in Brazil: LIBRAS and Portuguese. In addition to the teacher responsible for the class, the teaching network needs to offer these professionals initial and continuing training on teaching for the deaf students and their language, capable of providing structural and pedagogical conditions for the learning characteristics of deaf students, without taking away the right to be a citizen.